Textural Analysis of Sulphated ZrO–SiO Sol–Gel Catalytic Supports by N Sorption and X-Ray Diffraction - J. Salmones; P. Bosch; V.H. Lara; J.M. Esparza; C. Felipe; I. Kornhauser; F. Rojas (Adsorption Science & Technology)
The textural properties of sulphated ZrO 2 –SiO 2 catalytic supports of different compositions were investigated through N 2 sorption and X-ray diffraction (conventional and SAXS) methods. The materials were synthesised by the sol–gel procedure from a mixture of zirconium(IV) tert-butoxide and tetraethyl orthosilicate. The final products were obtained after drying at 125°C followed by calcination at 400°C. The porous structures of the substrates were found to depend on their composition: at low zirconia contents these were formed by slit cavities while at high ZrO 2 concentrations the void structure became open; both cavities and necks were of similar size. In the first case, the pore size distribution function could be obtained from an analysis of the ascending boundary curve of the N 2 isotherm since adsorption occurred on a flat surface. In the second case, a unique pore-size distribution was obtained either from the ascending or descending boundary curves of the N 2 isotherm. A tubular geometry seemed appropriate for the description of the sorption characteristics of these substrates. Primary descending scanning curves traced within the hysteresis loops of samples having high ZrO 2 contents offered further textural information. X-Ray diffraction methods provided compound identification, evidence of phase segregation between ZrO 2 and SiO 2 , and particle and pore-size distributions.